2022
DOI: 10.3389/fmars.2022.963193
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing seawater carbonate dynamics in a macroalgal habitat

Abstract: Photosynthetic organisms shift the dynamics of surface pCO2 driven by the sea surface temperature change (thermodynamic driver) by assimilating inorganic C from seawater. Here we measured net C uptake in a macroalgal habitat of coastal Korea for two years (2019-2020) and found that the macroalgal habitat contributed 5.8 g C m−2 month−1 of the net C uptake during the growing period (the cooling period, September−May). This massive C uptake changed the thermodynamics-driven seasonal dynamics such that the air−se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Most studies to date have found macroalgae forests to be strong net CO 2 sinks (Delille et al ., 2000; Ikawa & Oechel, 2015; Watanabe et al ., 2020; Kim et al ., 2022), with the intensity of CO 2 drawdown being related to forest area and productivity (Ikawa & Oechel, 2015). Evidence linking human actions in macroalgae ecosystems to CO 2 drawdown is mostly available for POC pathways, as tracking the fate of macroalgae‐derived DOC presents numerous challenges as discussed above.…”
Section: Macroalgal Forests and Climate Change Mitigationmentioning
confidence: 99%
“…Most studies to date have found macroalgae forests to be strong net CO 2 sinks (Delille et al ., 2000; Ikawa & Oechel, 2015; Watanabe et al ., 2020; Kim et al ., 2022), with the intensity of CO 2 drawdown being related to forest area and productivity (Ikawa & Oechel, 2015). Evidence linking human actions in macroalgae ecosystems to CO 2 drawdown is mostly available for POC pathways, as tracking the fate of macroalgae‐derived DOC presents numerous challenges as discussed above.…”
Section: Macroalgal Forests and Climate Change Mitigationmentioning
confidence: 99%